2022
DOI: 10.7759/cureus.28760
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation in the Treatment of Parkinson’s Disease

Abstract: Parkinson's disease (PD) is a common progressive neurodegenerative movement disorder. The cardinal feature of Parkinson's is neuronal degeneration causing a dopamine deficit in the brain which leads to a host of clinical features in the patient. However, consensus over specific clinical criteria for diagnosis remains to be established. Parkinson's does not have a cure yet, but a variety of diagnostic and treatment protocols have been developed over the years with a primary focus on pharmacological therapy. Ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The levodopa challenge, which is the most used preoperative test for DBS patient selection worldwide, showed that individual patient improvement after the therapy was inaccurately predicted with a large range of up to 30 UPDRSIII points [11]. A machine learning algorithm that could identify/predict which patients will benefit the most from DBS surgery would pave the way not only to a more cost-effective selection of candidate patients but also give confidence to potentially consider cohorts of older people [12] and those with comorbidities [13] who are for now discouraged on risk-benefit assessment. Our results can be interpreted as a proof-of-concept machine learning patient selection tool produced by an easy-to-implement imaging analysis pipeline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The levodopa challenge, which is the most used preoperative test for DBS patient selection worldwide, showed that individual patient improvement after the therapy was inaccurately predicted with a large range of up to 30 UPDRSIII points [11]. A machine learning algorithm that could identify/predict which patients will benefit the most from DBS surgery would pave the way not only to a more cost-effective selection of candidate patients but also give confidence to potentially consider cohorts of older people [12] and those with comorbidities [13] who are for now discouraged on risk-benefit assessment. Our results can be interpreted as a proof-of-concept machine learning patient selection tool produced by an easy-to-implement imaging analysis pipeline.…”
Section: Discussionmentioning
confidence: 99%
“…To summarise, PD is characterised by neuronal loss not only in the substantia nigra but throughout the brain [26]. Although there are several hypotheses with regard to the mechanism of DBS [13], there is no doubt that its effects are not only local around the electrode but also remote, throughout the basal ganglia circuitry and cortex. This hypothesis requires a functional connectivity between these areas.…”
Section: Pathophysiological and Anatomical Correlatesmentioning
confidence: 99%
“…If there is a clear response to stim, even a partial response, medication can be gradually reduced. If there is not a response to stimulation because the stimulation parameters are still being determined, medication should not be reduced ( 21 ). However, the current drug reduction strategy only relies on clinical response and doctor experience, which has some limitations.…”
Section: Introductionmentioning
confidence: 99%